Web-Based Information System For Tourism Promotion In Rindu Hati Village Taba Penajung District Bengkulu Central Regency - Anisya Sonita; Weki Syaputra (Penerbit Jurnal Indonesia, 2022)
Website is an internet service that can display multimedia in the form of (data, text, still or motion pictures, animation, sound, video, or a combination of all of them, both dynamic and static which form an interrelated circuit where each is linked. with page networks (hyperlinks). The website itself has many benefits, one of which is for the promotion of pre-tourism in certain areas. The pre-tourism sector is an important factor for regional and state income because it can provide benefits for the infrastructure that supports it. Rinduhati Village Tourism this is still not well publicized, a website-based tourism information system in the tourist village of Rinduhati Village is indispensable as a medium and means of delivering information to the public or tourists who want to know about tourist objects in Rinduhati village, be it natural tourism. The purpose of this study is to how to design a website for tourism information systems in the tourist village of Rinduhati village based on the web as a promotional media. The research instrument uses a waterall model which includes analysis, design, coding, and testing. This study uses a qualitative research approach. And the object of research is the tourist village of Rinduhati village which is located in Taba Penanjung District, Central Bengkulu Regency. With the existence of a website-based information system for the promotion of tourist villages in Rinduhati village, it is hoped that it can help the Rinduhati village community to promote tourism villages so that people are more aware and interested in doing nature tourism in Rinduhati village.